Arquivos audiovisuais em emissoras de televisão: marcos legais da comunicação e arquivologia - Guimarães, Mariana Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Os arquivos audiovisuais de televisão é o setor que zela pela organização, preservação e recuperação dos arquivos audiovisuais. Contudo, a maioria desses arquivos sofre destruição deliberada em seu acervo devido à falta de espaço. O objetivo foi buscar na legislação brasileira de radiodifusão a existência de orientações normativas que indicassem o início de um arquivo audiovisual de televisão, e na legislação arquivística algum regulamento sobre a preservação desse arquivo. A abordagem metodológica utilizada é pautada em pesquisa bibliográfica nas três áreas bases desse trabalho e em pesquisa documental.Na arquivologia, a pesquisa é sobre arquivos audiovisuais, na comunicação pela busca da história da televisão, e no direito para compreender os processos de concessões e a hierarquia das normas jurídicas. A pesquisa documental foi feita nos documentos oficiais do Governo Federal e consultadas nos órgãos federais pelo portal online da legislação. Conclui-se que a legislação brasileira de radiodifusão não traz nenhuma orientação significativa para os arquivos audiovisuais de televisão, e esta desatualizada; e também, que a legislação arquivística aborda de forma breve o arquivo audiovisual em suas normas.

Television audiovisual archives known as the Documentation Center is the sector that ensures the organization, preservation and recovery of audiovisual archives. However, most of these files suffer deliberate destruction in their collection due to lack of space. The objective was to seek in the Brazilian telecommunications legislation the existence of normative guidelines that would indicate the beginning of a television audiovisual archive, and in the archival legislation some regulation on the preservation of this archive. The methodological approach used is based on bibliographic research in the three basic areas of this work and on documentary research. In archival science, the research is on audiovisual archives and the construction of CEDOCs, on communication in search of the history of television, and on the right to understand the processes of concessions and the hierarchy of legal norms. The documentary research was carried out in official documents of the Federal Government and consulted in federal agencies through the online legislation portal. It is concluded that the Brazilian telecommunications legislation does not provide any significant guidance for television audiovisual archives, and the telecommunications legislation is outdated. Archival legislation does not address the audiovisual archive in its rules, and the resolution of the National Council of Archives that initiated the guidelines on audiovisual is not in force, as the Technical Chamber that was engaged in the treatment of audiovisual archives is inactive.
Audiovisual archives on television stations: legal frameworks for communication and archival science
Keywords: Arquivologia; Arquivo audiovisual; Televisão; Legislação brasileira de telecomunicações; Legislação arquivística brasileira; Archival science; Audiovisual archive; Television; Brazilian telecommunications legislation; Brazilian archival legislation